A carbon mixed selenium sulfide separator coating for lithium‐sulfur battery life enhancement. Issue 3 (28th December 2022) - Jiang, Wen; Dong, Lingling; Liu, Shuanghui; Zhang, Weimin; Ai, Bing; Pan, Kefeng; Zhang, Lipeng
Abstract: Lithium‐sulfur batteries are one of the most promising energy storage devices in the future due to their high specific capacity and abundant natural reserves. However, the shuttle effect of soluble intermediate polysulfide products can lead to rapid decay of battery capacity, short cycle life and serious self‐discharge effect, which hinders the development of lithium‐sulfur batteries. Here, we coated the separator with a mixed SeS2 /KB coating, which can effectively stop the polysulfide shuttle and improve the performance of lithium‐sulfur batteries through the physical barrier of KB and the strong adsorption of SeS2 in synergy with each other. Theoretical calculations and experiments show that SeS2 has a strong adsorption effect on polysulfides. The lithium‐sulfur battery equipped with SeS2 /KB separator has excellent electrochemical performance, maintaining a capacity of 482 mAh gS −1 after 1000 cycles at 1 C current density, with a decay rate of only 0.047 % per cycle. Abstract : The modified PP separator is prepared by coating SeS2 /KB on one side of the diaphragm, which can effectively stop the shuttle of polysulfide through the chemical adsorption of SeS2 and the physical barrier effect of KB, and realize the long‐term stable cycle of lithium‐sulfur battery.